Analysis of bicycle helmet damage visibility for concussion-threshold impacts. Issue 1 (1st January 2021) - Cachau-Hansgardh, Ana; McCleery, Caitlin; Limousis-Gayda, Manon; Hashish, Rami
ABSTRACT: Any helmet involved in an accident should be replaced, regardless of appearance after impact. However, consumer compliance and interpretation of this recommendation is unclear, for which there is additional ambiguity for lesser impacts. This study aims to investigate the relation between helmet damage visibility and lesser impacts in line with concussion. As a preliminary model, a commercially available road-style helmet was chosen. Twelve helmets underwent impact attenuation testing; four were dropped from the standard testing height of 2 m, and eight from lower drop heights (0.34 and 0.42 m) associated with the production of linear accelerations (90 and 100 g, respectively) consistent with the production of concussion. Expanded polystyrene damage was assessed via flat punch penetration testing. American adults were then polled on helmet damage visibility based upon before and after photos. All helmets demonstrated damage to the expanded polystyrene liner in the form of altered material properties. Helmets dropped from 2 m displayed significant changes in elastic buckling (p < .01) and densification behavior (p < .01) as compared with lower drop height results. Adverse change in elastic buckling behavior was found to increase linearly with drop height (p < .001). Damage visibility was significant for helmets dropped from a 2-meter height, however, such a relation among the helmets impacted at the threshold for concussion was lacking. These findings suggest that for the chosen helmet model, consumers may be unable to distinguish between new helmets and helmets with diminished protective abilities.